The Effect of Practicum on the Discipline Orientations of Pre-Service Teachers - Ali Göksu; Kağan Büyükkarcı; Bilal Genç (International Online Journal of Education and Teaching, 2013)
This study aimed to examine the classroom discipline perceptions of pre-service language teachers both before and after the student teaching experience. Before going to their practice schools and immediately after completing their full-time student teaching experience, pre-service teachers (N = 104) from three state universities in Turkey completed a discipline belief questionnaire identifying their preferred model of classroom discipline. The results indicated that although the student teaching experience in practice schools increased beginning teachers’ preferences from a humanistic discipline model to a more assertive discipline model, this increase is not significant. These results show that the student teaching experience does not create a difference in previous perceptions and beliefs of pre-service teachers. The results of the study also suggest that student teachers’ preconceptions regarding the profession will not change despite the practical experience gained during practicum.